Challenges and barriers in implementing an integrated sustainable nitrogen management policy on the Romanian grasslands - Mihai Constantinescu; Nicusor-Flavius Sima (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
The nitrogen management on the Romanian permanent grasslands is dependent on various factors, but the traditional practices and agri-environment EU funded payment schemes are playing the most important roles. At the same time, policies and farmers are mainly acting against reducing the nitrogen losses especially by implementing measures for avoiding water pollution with nutrients, while the concept of improving nitrogen use efficiency through integrated practices for reducingboth water and air nitrogen losses remains a topic insufficiently addressed. Nevertheless, the situation is not specific only to Romania, as the country is merely applying the international agreements and EUlegislation. Therefore, this article is focusing on the analysis of the challenges and barriers in implementing an integrated sustainable nitrogen efficiency use at policy and farmer level, thus identifying possible options in promoting good practices that should lead at the reduction of nitrogen losses in both water and air in an integrated manner.Grasslands are particular challenging for Romania as are largely extensively and traditionally managed. Furthermore, manure cannot be incorporated in soils by ploughing, as in case of arable land, thus remaining more prone to nitrogen air losses.
Keywords: Q1; Q15; Q24; 330; nitrogen use efficiency; integrated nitrogen management; sustainable nitrogenmanagement; manure; nitrates leaching; ammonia volatilization